Artificial intelligence in the practice of work: a new way of standardising or a means to maintain complexity?. (7th April 2023) - Heinlein, Michael; Huchler, Norbert
Abstract : The article proposes an analytical perspective on artificial intelligence (AI) that can be fruitful in the sociology of work. The practical logic of new forms of AI (connectionist AI) is described as an interplay of social and technical processes of opening and closing possibilities of knowledge and action. In order to develop this argument, it is first shown in which sense AI can be understood as a contingency-generating technology in socio-technical contexts. The architecture based on neural networks is elaborated as a decisive feature of connectionist AI that not only opens up technical possibilities but can also shape social processes and structures by 'selectivity'. However, this shaping does not take place solely on the part of the AI, but only becomes apparent in the interplay with specific restrictions that lie both in the social context of use and in the algorithmic architecture of the AI itself. For research in the sociology of work, this means that contingency theory approaches must be linked with approaches that emphasise the limits of ('intelligent') digitalisation. The yield of such a perspective is outlined in relation to the control of work with AI.